Numerical Analysis of Unsteady Conjugate Natural Convection of Hybrid Water-Based Nanofluid in a Semicircular Cavity; Journal of Thermal Science and Engineering Applications; Vol. 9, iss. 4 - Chamkha A. J. Ali J. (2017, 2017)
Title screen